(3eONd Edi GdQjGVjGJ GdeGdjIs - (3efUhQ Hf Yha(B, (3YHO GdcQjes ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2006)
(3GdaGFOI GdHSjWI,GdaGFOI GdeQcHI,GdOaYGJ GdeJSGhjI,GSJgdGc GdbQhVs
Keywords: (3GdQjGVI GdJLGQjI hGdeGdjIs